Large inter-stock differences in catch size-at-age of mature Atlantic salmon observed by using genetic individual origin assignment from catch data. - Marja-Liisa Koljonen; Michele Masuda; Irma Kallio-Nyberg; Jarmo Koskiniemi; Irma Saloniemi (PLoS ONE)
Genetic individual assignment of river stock of origin of mixed stock catch fish offers a tool to analyze size differences among river stocks. Data on the genetically identified river stock of origin of individual fish from commercial mixed stock catches were used to compare the catch size-at-age of mature Atlantic salmon catch fish (Salmo salar) from different rivers in the Baltic Sea. In this application of genetic mixed stock modeling, individual assignments of the river stock of origin were analyzed together with length- and weight-at-age data for individual catch fish. The use of four genetic stock identification based methods was compared for defining the length distributions of caught mature salmon in different river stocks. The catch data included information on maturing salmon in the northern Baltic Sea over the years 2000-2013. DNA microsatellite data on 17 loci and information on the smoltification age were used to assign spawners to their stock of origin. All of the compared methods for using probabilistic stock of origin data in our case yielded very similar estimates of the final mean length distributions of the stocks. The Bayesian mixture model yielded slightly more conservative estimates than the direct probability method, threshold method, or the modified probability method. The catch size between spawners of a same sex and age from river stocks differed significantly and the differences were large. The mean catch weight of 1-sea-winter old mature males in different rivers varied from 1.9 kg to 2.9 kg, from 5.1 kg to 7.5 kg for 2-sea-winter old males, from 5.0 kg to 7.2 kg for 2-sea-winter old females, and from 8.2 kg to 10.8 kg for 3-sea-winter-old females. The mean size of caught wild salmon spawners in each year-class was on average smaller than that of the hatchery-reared and sea ranched stocks.